I know the answer but don't know the full solution. Please help
Attachments:
![](https://hi-static.z-dn.net/files/dcc/e3ac0c60464a8c13f3828d57179a5276.jpg)
Answers
Answered by
6
Solution :-
Equations :-
1.) 2k(x² + 2) + rx + x² - 5 = 0
2.) 2k( 3x² + 1) + px - x² - 1 = 0
Both of them have common roots.
Now by expansion of the equations.
1.) 2k(x² + 2) + rx + x² - 5 = 0
→ 2kx² + 4k + rx + x² - 5 = 0
→ x²(2k + 1) + rx + (4k - 5) = 0
2.) 2k( 3x² + 1) + px - x² - 1 = 0
→ 6kx² + 2k + px - x² - 1 = 0
→ x²(6k - 1) + px + (2k - 1) = 0
Now applying the condition for the common roots.
Now by taking
By cross multiplication :-
Now as k > 1
→ k = 3/2
Now
Then
= 2r - p
= 2r - 2r
= 0
Similar questions
English,
7 months ago
Math,
7 months ago
Social Sciences,
7 months ago
Social Sciences,
1 year ago
Science,
1 year ago
Math,
1 year ago